The Biomechanical Characteristics of the Strongman Yoke Walk - Hindle, Benjamin R.; Lorimer, Anna; Winwood, Paul; Brimm, Daniel; Keogh, Justin W. L. (Frontiers in Sports and Active Living, 2021)
The yoke walk is a popular strongman exercise where athletes carry a heavily loaded frame balanced across the back of their shoulders over a set distance as quickly as possible. The aim of this study was to use ecologically realistic training loads and carry distances to (1) establish the preliminary biomechanical characteristics of the yoke walk; (2) identify any biomechanical differences between male and female athletes performing the yoke walk; and (3) determine spatiotemporal and kinematic differences between stages (intervals) of the yoke walk. Kinematic and spatiotemporal measures of hip and knee joint angle, and mean velocity, stride length, stride rate and stance duration of each 5 m interval were taken whilst 19 strongman athletes performed three sets of a 20 m yoke walk at 85% of their pre-determined 20 m yoke walk one repetition maximum. The yoke walk was characterised by flexion of the hip and slight to neutral flexion of the knee at heel strike, slight to neutral extension of the hip and flexion of the knee at toe-off and moderate hip and knee range of motion (ROM), with high stride rate and stance duration, and short stride length. Between-interval comparisons revealed increased stride length, stride rate and lower limb ROM, and decreased stance duration at greater velocity. Although no main between-sex differences were observed, two-way interactions revealed female athletes exhibited greater knee extension at toe-off and reduced hip ROM during the initial (0–5 m) when compared with the final three intervals (5–20 m), and covered a greater distance before reaching maximal normalised stride length than males. The findings from this study may better inform strongman coaches, athletes and strength and conditioning coaches with the biomechanical knowledge to: provide athletes with recommendation on how to perform the yoke walk based on the technique used by experienced strongman athletes; better prescribe exercises to target training adaptations required for improved yoke walk performance; and better coach the yoke walk as a training tool for non-strongman athletes.